(untitled) (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2022)
The aim of this research, taking into account that hi-tech technologies are reshaping the profile of journalists, is to analyse, through an exploratory and descriptive study, carried out by means of interviews with academics and information professionals, what are the new journalistic routines demanded in the current context of technological change. The results suggest that hi-tech journalism, generally, involves an increase in execution times. The need for training in this field has also been identified, and that the essential skills of journalists need to be the same as those of traditional journalism.